Proteomics approaches: A review regarding an importance of proteome analyses in understanding the pathogens and diseases - Zubair, Muhammad; Wang, Jia; Yu, Yanfei; Faisal, Muhammad; Qi, Mingpu; Shah, Abid Ullah; Feng, Zhixin; Shao, Guoqing; Wang, Yu; Xiong, Qiyan (Frontiers in Veterinary Science, 2022)
Proteomics is playing an increasingly important role in identifying pathogens, emerging and re-emerging infectious agents, understanding pathogenesis, and diagnosis of diseases. Recently, more advanced and sophisticated proteomics technologies have transformed the disease diagnostics and vaccines development. The detection of pathogens is made possible by more accurate and time-constrained technologies, resulting in an early diagnosis. A more detailed and comprehensive information regarding the proteome of any noxious agent is made possible by combining mass spectrometry with various gel-based or short-gun proteomics approaches recently. MALDI-ToF has been proved quite useful in identifying and distinguishing bacterial pathogens. Other quantitative approaches are doing their best in the investigation of bacterial virulent factors, diagnostic markers and vaccine candidates. Proteomics is also helping in the identification of secreted proteins and their virulence-related functions. The goal of this review is to highlight the role of cutting-edge proteomics approaches in better understanding of the functional genomics of pathogens. This also highlights limitations of proteomics in the investigation of bacterial secretome.